Mechanical Stress Changes the Complex Interplay Between HO-1, Inflammation and Fibrosis, During Excisional Wound Repair - Cremers, Niels A. J.; Suttorp, Maarten; Gerritsen, Marlous M.; Wong, Ronald J.; van Run-van Breda, Coby; van Dam, Gooitzen M.; Brouwer, Katrien M.; Kuijpers-Jagtman, Anne Marie; Carels, Carine E. L.; Lundvig, Ditte M. S.; Wagener, Frank A. D. T. G. (Frontiers in Medicine, 2015)
Mechanical stress following surgery or injury can promote pathological wound healing and fibrosis, and lead to functional loss and esthetic problems. Splinted excisional wounds can be used as model for inducing mechanical stress. The cytoprotective enzyme heme oxygenase-1 (HO-1) is thought to orchestrate the defense against inflammatory and oxidative insults that drive fibrosis. Here, we investigated the activation of the HO-1 system in a splinted and non-splinted full thickness excisional wound model using HO-1-luc transgenic mice. Effects of splinting on wound closure, HO-1 promoter activity, and markers of inflammation and fibrosis were assessed. After seven days, splinted wounds were more than 3 times larger than non-splinted wounds, demonstrating a delay in wound closure. HO-1 promoter activity rapidly decreased following removal of the (epi)dermis, but was induced in both splinted and non-splinted wounds during skin repair. Splinting induced more HO-1 gene expression in 7-day wounds; however, HO-1 protein expression remained lower in the epidermis, likely due to lower number of keratinocytes in the re-epithelialization tissue. Higher numbers of F4/80-positive macrophages, αSMA-positive myofibroblasts, and increased levels of the inflammatory genes IL-1β, TNF-α, and COX-2 were present in 7-day splinted wounds. Surprisingly, mRNA expression of newly-formed collagen (type III) was lower in 7-day wounds after splinting; whereas, VEGF and MMP-9 were increased. Summarizing, these data demonstrate that splinting delays cutaneous wound closure and HO-1 protein induction. The pro-inflammatory environment following splinting, may facilitate higher myofibroblast numbers and increases the risk of fibrosis and scar formation. Therefore, inducing HO-1 activity against mechanical stress-induced inflammation and fibrosis may be an interesting strategy to prevent negative effects of surgery on growth and function in patients with orofacial clefts or in burns patients.